PEMBELAJARAN THINK-TALK-WRITE (TTW) SEBAGAI SARANA MENUMBUHKAN JIWA KEPEMIMPINAN ANAK - Siti Saudah (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2014)
Nowadays, what become problem in Indonesia is the lack ofleadership skill. Anarchy and brawling happened to the juvenile and isstarting to be a culture. The affection of foreign cultures and the lackof leader figure are factors for the nation characteristic crisis. Manyincidents of delinquency must to be concerned by family and school,because the youth is the future of the nation. Government should haverealized the importance of the youth education by encouraging theleadership through the character and leadership education base.Thepurpose of this research is to encourage the leadership of the youththrough â€œthink-talk-write (TTW)â€ education strategy. The strategy isabout the way chosen by educators to define the scope, and the topicsin the class. This model is used by the author and applied by givingtime for the students to do activities (thinking, reflecting the ideas andtesting it).The research methodology used is descriptive method, whichexplains the research result based on the data taken from the TTWeducation process. The data is collected by 2 observers using form oftutorial activity and form of student activities. The data analysis ofstudent activities is calculated by changing the frequency of activities bythis equation% activity = frequency of certain activities x 100%total number of activitiesThe leadership indicator can be concluded from variables appliedby the teacher in TTW education system and the leadership indicatorshown by students. Those leadership elements are like to read, clever,stable emotion, able to communicate well, writing ability, and decidewith well thought, open-minded to find solution, active, and able tocooperate in team.